Cervical Lactobacillus and leukocyte infiltration in preterm premature rupture of membranes - Silva, Marcia Guimarães da [UNESP]; Peraçoli, José Carlos [UNESP]; Sadatsune, T.; Abreu, E. S.; Peracoli, MTS (Elsevier B.V., 2003)
Objectives: To evaluate the possible association between microorganisms present in the cervical secretions and amniotic fluid of pregnant women with preterm premature rupture of membranes (PPROM), and histologic chorioamnionitis. Methods: Thirty-seven pregnant women with PPROM and 21 healthy pregnant women were studied. Secretions from the cervical canal and amniotic fluid were collected to isolate microorganisms present in the genital tract. Cervical smears were Gram stained and evaluated microscopically. At delivery, chorioamniotic membranes were collected for histopathologic analysis. Results: Microscopic examination of the cervical secretion smears obtained from the PPROM group showed a low rate of Lactobacillus species, large numbers of leukocytes, and a wide diversity of microorganisms compared with the control group. The PPROM group presented an 80% rate of chorioamnionitis. Staphylococcus aureus isolation in cervical secretion was associated with intense inflammatory infiltrate in the membranes and might play a role in the pathogenesis of PPROM. Conclusions: the low colonization of cervical flora by Lactobacillus species associated with an intense leukocyte infiltrate detected in Gram-stained cervical smears can be considered a rapid method of detecting chorioamnionitis in pregnant women with PPROM. (C) 2003 International Federation of Gynecology and Obstetrics. Published by Elsevier B.V. Ireland Ltd. All rights reserved.
Keywords: premature rupture of membranes; gram stain; chorioamnionitis